A study on the consumption of Japanese fashion among young Singaporean females. - Chan, Melissa Mei Shan. (2013)
The increasing presence of Japanese brand clothing stores in Singapore is something that cannot be ignored, but is there a market for it? In this study, I will not only be reiterating that there is a significant following of Japanese fashion by young Singaporean females between the ages of 18 to 26, but many have utilized the internet to not only get their fashion ‘fix’ from the source (that is, Japan), but also to share (via blogging) and connect with others with the same interests as themselves. The love for Japanese fashion also seems to be something that is tied to the appreciation of Japanese culture- or at least, its popular culture. On those grounds, I will explore the ways in which Japan has successfully created an attractive international image. Lastly, I will be exploring the ways in which consumption and then the display of a particular fashion by an individual is both conscious and conspicuous.